2021
DOI: 10.1097/jxx.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Development of the novice nurse practitioner role transition scale: An exploratory factor analysis

Abstract: Background: Novice nurse practitioner role transition (NNPRT) can be described as stressful and turbulent, leading to decreased job satisfaction and increased intent to leave. No published instrument exists to measure NNPRT. Thus, researchers, educators, and administrators are limited in their ability to measure the concept and therefore understand the factors that lead to a successful, or unsuccessful, role transition experience. An instrument with evidence of validity and reliability is needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…When we also considered the theoretical framework used to guide instrument development and the history of item generation (Barnes et al, 2022), the suggested factors aligned with the domains under which the items were originally developed. First, "I understand what is expected of me in my role as an NP" (moved to "Perceived Competence and Self-Confidence") was originally generated under "Role Ambiguity", a subdomain of "Role Acquisition."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we also considered the theoretical framework used to guide instrument development and the history of item generation (Barnes et al, 2022), the suggested factors aligned with the domains under which the items were originally developed. First, "I understand what is expected of me in my role as an NP" (moved to "Perceived Competence and Self-Confidence") was originally generated under "Role Ambiguity", a subdomain of "Role Acquisition."…”
Section: Discussionmentioning
confidence: 99%
“…We used a cross-sectional design to collect data from a convenience sample of novice NPs, separate from the sample collected and used for the previous EFA analysis ( Barnes et al, 2022). Data were collected online via a confidential Qualtrics survey over a 4-month period in early 2021.…”
Section: Setting and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…(1) Novice nurses face a critical role transition process through their first months on the job. (2) Role transition is defined as the process of moving from one state to another, which is usually associated with significant changes in goals, roles, and responsibilities. (3) Novice nurses' role transition can be described as stressful and turbulent, leading to decreased job satisfaction and increased intent to leave.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sources of supports are essential from colleagues; educators, and administrators associated with guidance from head nurses and superiors. (2) Many areas emerged as opportunities to support novice nurse transition such as: awareness of role transition, preceptorship, social support, and orientation. (18) Novice nurses struggle with the challenge of providing safe and competent care to their customers while continuing to fill the gaps in developing their knowledge base.…”
Section: Introductionmentioning
confidence: 99%